ANALISIS KEMAMPUAN STEAM BERBASIS GENDER PADA MATERI ARCHAEBACTERIA DAN EUBACTERIA SISWA - H Hasruddin; Evi Lestari (Universitas Negeri Medan, 2020)
This research aims to know the STEAM ability of students based on Archaebacteria and Eubacteria based on gender in SMAN 2 Percut Sei Tuan, to find out students' views on learning Archaebacteria and Eubacteria material with a scientific approach. The descriptive method in the study used a population of all students of class X Natural Sciences. The sample consisted of 50 male students and 50 female students by random sampling. Data collection using questionnaires and 10 essay questions. Data were analyzed using percentage techniques and differences in gender ability were performed t-test at a significance level of 5% aided by SPSS 24.0. The results showed the science ability of female students (78.67%)> male students (47.07%), th> tt, p 0.05. The ability of technology in female students (61.33%)> male students (47.00%), -th> -tt p 0.05. Engineering ability of female students (64.29%)> male students (50.00%), th> tt, p 0.05. Arts ability of female students (72.40%)> male students (65.00%), th> tt, p 0.05. Mathematical ability of female students (65.75%)> male students (56.25%), th> tt, p 0.05. There are differences in the STEAM ability of students, female students (70.60%) while male students (53.00%), -th> -tt, p 0.05. The views of female students are more positive than male students in learning Archaebacteria and Eubacteria material with a scientific approach.